1988
DOI: 10.1099/00221287-134-1-53
|View full text |Cite
|
Sign up to set email alerts
|

Motility of Campylobacter jejuni in a Viscous Environment: Comparison with Conventional Rod-shaped Bacteria

Abstract: The motility of four strains of Campylobacter jejuni in solutions of varying viscosity was measured and compared to that of a number of conventional rod-shaped bacteria (CRSB). All the bacteria tested showed an initial increase in velocity in the low viscosity solutions--between 1 and 3 centipoise (1 P = 0.1 Pa s). However, only the campylobacters were actively motile in highly viscous solutions with velocities ranging from 60 to 100 micron s-1. All strains of C. jejuni tested showed three separate peaks of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
85
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 19 publications
(32 reference statements)
5
85
0
1
Order By: Relevance
“…On the other hand, the e-proteobacteria and spirochetes, many of which thrive exclusively in association with a host, have evolved characteristically rapid and powerful swimming capabilities that enable them to bore through mucous layers coating epithelial cells or between tissues. Indeed, the e-proteobacteria Campylobacter jejuni and Helicobacter pylori are capable of continued swimming in highviscosity media that immobilize E. coli or Vibrio cells (4)(5)(6), and similar behavior is observed for spirochetes (7,8).…”
mentioning
confidence: 81%
“…On the other hand, the e-proteobacteria and spirochetes, many of which thrive exclusively in association with a host, have evolved characteristically rapid and powerful swimming capabilities that enable them to bore through mucous layers coating epithelial cells or between tissues. Indeed, the e-proteobacteria Campylobacter jejuni and Helicobacter pylori are capable of continued swimming in highviscosity media that immobilize E. coli or Vibrio cells (4)(5)(6), and similar behavior is observed for spirochetes (7,8).…”
mentioning
confidence: 81%
“…These bacteria exhibit motility in highly viscous solutions that immobilize rod-shaped bacteria with peritrichous flagella (i.e. E. coli and Salmonella enteritidis; Ferrero and Lee, 1988). Two flagellin genes, flaA and flaB, have been identified in all species and strains examined (Guerry et al, 1992).…”
Section: Gastrointestinal Mucusmentioning
confidence: 99%
“…In fact, the importance of the flagella in Campylobacter virulence has been highlighted in many studies, including those using both in vivo animal models and in vitro models based on cell culture systems [106][107][108]. Further, Konkel et al clearly demonstrated that functional flagella are required for the secretion of important Campylobacter virulence factors that are required to establish a maximal invasion of INT 407 intestinal epithelial cells.…”
Section: Flagellamentioning
confidence: 99%
“…Further, Konkel et al clearly demonstrated that functional flagella are required for the secretion of important Campylobacter virulence factors that are required to establish a maximal invasion of INT 407 intestinal epithelial cells. With particular respect to Campylobacter-related bacteremia, it is hypothesized that the Campylobacter flagella provides motility, enabling the bacterium to traverse through the gastrointestinal mucus layer and reach the epithelium of the intestine ready for translocation into the blood stream [107].…”
Section: Flagellamentioning
confidence: 99%